Be ready when the luck happens : a memoir - Garten, Ina (Crown, an imprint of the Crown Publishing Group, a division of Penguin Random House LLC, 2024)
"Ina Garten, the author of thirteen best-selling cookbooks, beloved Food Network personality, Instagram sensation, and the cultural icon whose face has launched a thousand memes, shares her personal story with readers hungry for a seat at her table"--